The Thomistic response to the nouvelle théologie : concerning the truth of dogma and the nature of theology - Bruckberger, R.-L. (Raymond-Léopold), 1907-1998; Garrigou-Lagrange, Réginald, 1877-1964; Labourdette, Michel, 1908-1990; Nicolas, Marie-Joseph, 1906-1999; Kirwan, Jon, 1971-; Kirwan, Jon, 1971-; Minerd, Matthew K.; Minerd, Matthew K. (The Catholic University of America Press, 2023)
"Makes available new translations from French of works by the leading Thomists in the mid-20th-century debate surrounding ressourcement theologians in the Catholic Church. The articles were authored by Dominican Fathers Reginald Garrigou-Lagrange, Michel Labourdette, Marie-Joseph Nicolas, and Raymond Bruckberger. The volume contains sixteen articles, thirteen of which have never appeared in English. All the major critical responses of the Dominican Thomists to the nouvelle théologie are here presented chronologically according to the primary debates carried on, respectively, in the journals Revue Thomiste and Angelicum. A lengthy introduction describes the unfolding of the entire debate, article by article, and explains and references the ressourcement interventions"--